Antimicrobial-resistant Bacteria: An Unrecognized Work-related Risk in Food Animal Production - Ricardo Castillo Neyra; Leora Vegosen; Meghan F. Davis; Lance Price; Ellen K. Silbergeld (Safety and Health at Work, 2012)
The occupations involved in food animal production have long been recognized to carry significant health risks for workers, with special attention to injuries. However, risk of pathogen exposure in these occupations has been less extensively considered. Pathogens are a food safety issue and are known to be present throughout the food animal production chain. Workers employed at farms and slaughterhouses are at risk of pathogen exposure and bacterial infections. The industrialization of animal farming and the use of antimicrobials in animal feed to promote growth have increased the development of antimicrobial resistance. The changed nature of these pathogens exposes workers in this industry to new strains, thus modifying the risks and health consequences for these workers. These risks are not yet recognized by any work-related health and safety agency in the world.